Does the CO-to-H2 conversion factor depend on the star formation rate? - Clark, Paul C.; Glover, Simon (Monthly notices of the Royal Astronomical Society, 2015)
Abstract. We present a series of numerical simulations that explore how the ‘X-factor’, XCO - the conversion factor between the observed integrated CO emission
Gesehen am 01.12.2020